BI'AH LUGHAWIYYAH ERA SOCIETY 5.0 MELALUI PENGGUNAAN MEDIA SOSIAL MAHASISWA - Ilmiani, Aulia Mustika; Muid, Abdul (Arabi : Journal of Arabic Studies, 2021)
Bī'ah Lughawiyyah, as the Arabic language environment is called, is a very effective means of acquiring Arabic language proficiency. In this 5.0 Era, the definition of the bī'ah lughawiyyah is no longer tied to a mutually agreed time and place. Visual interaction using technology can promise unlimited access so that it can narrow space and time. Previously, bī'ah lughawiyyah was often identified with a community or group that was created under a specific system or arrangement, so what about now? Amidst the massive use of social media in everyday life. This article explains the Arabic language environment in the 5.0 era in terms of students' daily activities. This study uses a descriptive qualitative approach to categorize student activities as a form of bī'ah lughawiyyah era 5.0. The subjects in this study were students of the Arabic Language Education Study Program at IAIN Palangka Raya. The data collection techniques used were observation, interview, and documentation. The results showed that bī'ah lughawiyyah era 5.0 was dominated by social media such as Instagram, YouTube, and Facebook.